QbD based development of HPLC method for simultaneous quantification of Telmisartan and Hydrochlorothiazide impurities in tablets dosage form - Palakurthi, Ashok K.; Dongala, Thirupathi; Katakam, Lakshmi Narasimha R. (Practical laboratory medicine, 2020)
A simple reverse phase liquid chromatographic gradient method has been developed and validated for the simultaneous determination of specified & un-specified impurities of Telmisartan and Hydrochlorothiazide in combination oral solid dosage forms. The developed method is effective to separate a total of sixteen (16) peaks and quantify eleven (11) specified impurities of Telmisartan and three (3) specified impurities of Hydrochlorothiazide with a minimum chromatographic resolution of 2.5. The separation was acquired with Inertsil ODS-3V, 150 ​× ​4.6 ​mm, 3.5 ​μm column at a flow rate of 1.0 mL min-1 with the mobile phase-A consists of 0.02 ​M potassium dihydrogen phosphate (pH of 3.5) and mobile phase-B consists of a mixture of Milli-Q water and acetonitrile (100: 900 v/v) respectively. The detection of impurities was carried out at 230 ​nm and column temperature was maintained at 40 ​°C. Further optimized chromatographic conditions were applied to design of experiments to find out the critical quality attributes and established the design space. The binary combination of drug product was subjected to the different stress conditions such as acid, base, oxidation, heat and photolysis as per the recommendations of international conference on harmonization (Q2). The degradation Product found in stress patterns are well separated among main analyte compounds. The method was validated to be specific, robust and rugged in terms of change of chromatographic, instrumental and technical variables. [Display omitted]